The efficacy and safety of peroperative statin treatment during coronary artery bypass grafting - I.V. Shklianka; O.J. Zharinov; К.O. Mikhaliev; O.A. Yepanchintseva; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the efficacy and safety of perioperative statins treatment during coronary artery bypass graft surgery (CABG).